Development and validation of the propensity for inter-role conflict scale - Egleston, David Oren (Kansas State University, 2008)
New scales were developed to measure conflict between work and school and family and school. These scales displayed adequate psychometric properties. A scale was developed to measure the propensity to experience inter-role conflict. The Propensity for Inter-role Conflict Scale (PIRCS) has excellent psychometric properties as established through exploratory and confirmatory factor analysis and scale and item analysis. PIRCS scores mediated the relationship between 14 of the 15 inter-role conflict to inter-role conflict pairs and displayed incremental validity, beyond known correlates of inter-role conflict, in the prediction of the six forms of inter-role conflict included in the study. The consequences of inter-role conflict were shown to affect the frequency of conflict between roles. However, this was only true when the data were aggregated. This indicates people take deliberate actions to limit certain forms of inter-role conflict. The boundaries between roles are differentially permeable. The work role boundary was most resistant to inter-role conflict. The family role boundary was least resistant to conflict from other roles. Personal characteristics affected the amount of inter-role conflict a person experienced. Women experienced significantly more conflict between family and school and school and family than men. Women were more adversely affected by the presence of children in the home than were men. Work conditions were also related to the experience of inter-role conflict. Working more hours was associated with higher levels of work-to-family and work-to-school conflict. Participants who worked weekends reported higher levels of work-to-family and work-to-school conflict. Employees who perceived greater flexibility at work reported less work-to-family and work-to-school conflict than those with less flexibility. The more semester hours participants were taking, the more conflict they reported between family and school, school and family and work and school. Spending more time on homework and study was associated with higher levels of conflict from school to family. The spillover of conflict between spouses was also demonstrated. The more hours a participant‟s spouse worked the more conflict the participant experienced from family to school and school to family.
Keywords: Inter-role Conflict; Gender Differences; Business Administration, Management (0454); Psychology, Industrial (0624); Psychology, Personality (0625)